Co(II)&Zn(II)&Cu(II) doped hydrotalcite and preparation method and application thereof
By using Co(II)&Zn(II)&Cu(II)&Cu(II) doped hydrotalcite catalyst, the problems of high reaction temperature, low oxidation efficiency and poor selectivity during the catalytic oxidation of cycloalkanes are solved, and the synthesis of cycloalkyl alcohols and cycloalkyl ketones is achieved with high efficiency and good selectivity.
Patent Information
- Application Number
- CN202110980720.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-08-25
Abstract
Description
Technical Field
[0001] The invention belongs to the field of industrial catalysis and fine organic synthesis, and specifically relates to Co(II)&Zn(II)&Cu(II) doped hydrotalcite and a preparation method and application thereof. Background Art
[0002] The catalytic oxidation of cycloalkanes is a very important conversion process in the chemical industry. Its oxidation products, cycloalkanols and cycloalkanones, are not only important organic solvents, but also important fine chemical intermediates. They are widely used in the synthesis of fine chemical products such as pesticides, medicines, dyes, surfactants, resins, etc., especially in the production of polyamide fibers nylon-6 and nylon-66. At present, the catalytic oxidation of cycloalkanes in industry is mainly based on homogeneous Co 2+ or Mn 2+ The reaction is carried out at 150 ºC~170 ºC with oxygen (O2) as the catalyst and oxidant at 150 ºC~170 ºC. The main problems are high reaction temperature, low oxidation efficiency, poor selectivity of target products, and the increase in reaction conversion rate will consume the selectivity of some oxidation products, especially the formation of aliphatic diacids is difficult to inhibit (Applied Catalysis A, General 2019, 575: 120-131; Catalysis Communications 2019, 132: 105809; Applied Catalysis A, General 2021, 609: 117904;). The main reasons for the above problems are: (1) Currently, industrial oxidation of cycloalkanes by O2 mainly undergoes a disordered free radical diffusion process; (2) The oxidation intermediate, cycloalkyl hydroperoxide, is converted into the target oxidation products cycloalkanol and cycloalkanone by a free radical thermal decomposition pathway, which increases the uncontrollability of the reaction system and reduces the selectivity of cycloalkanol and cycloalkanone; (3) The oxidizing property of the oxidation intermediate, cycloalkyl hydroperoxide, is not fully utilized; (4) The activity of cycloalkanol and cycloalkanone is higher than that of the substrate cycloalkanes. Therefore, effectively controlling the disordered diffusion of free radicals during the O2 catalytic oxidation of cycloalkanes, while catalytically converting the oxidation intermediate cycloalkyl peroxide and utilizing its oxidizing property to oxidize new cycloalkanes, is not only beneficial to improving the selectivity of catalytic oxidation of cycloalkanes, but also to improving the oxidation efficiency. It will be a very novel and highly significant process improvement in the field of industrial catalytic oxidation of cycloalkanes.
[0003] LDHs are a new type of inorganic functional material with a layered porous structure. The main layers are formed by metal cations with suitable ionic radius and charge number, and the interlayers are inorganic anions. The two are assembled through non-covalent bond interactions. The anions and cations are adjustable, and they have a good porous structure and can provide a certain confined environment. They have the advantages of adjustable chemical composition and structure, atomic-level dispersion of metal elements in the layers, good thermal stability, excellent catalytic performance, good biocompatibility and memory effect. They are widely used in ion exchange, adsorption separation, medicine, catalysis and other fields (Xu M., He S., Chen H., Cui GQ, Zheng LR, Wang B., Wei M., ACS Catal., 2017, 7 (11), 7600-7609). The present invention utilizes a ball milling method to prepare materials, using hydrotalcite as a precursor and preparing a metal-type catalyst by calcination. The preparation is simple and the cost is low. In addition, the excellent porous structure can achieve atomic-level dispersion of metal active catalytic centers and uniform distribution of active sites. The material has a large specific surface area, is not easy to sinter, and has excellent catalytic performance.
[0004] In addition, the introduction of trimetallic Co(II)&Zn(II)&Cu into the material is not only conducive to regulating the catalytic conversion of cycloalkyl peroxides, the intermediate products of oxidation, during the catalytic oxidation of cycloalkanes, but also promotes the conversion of cycloalkyl peroxides to cycloalkanols and cycloalkanones, and prevents their disordered thermal decomposition; the porous structure of the hydrotalcite material provides a certain confined environment, which can inhibit the disordered diffusion of free radicals and improve the reaction selectivity; in addition, the trimetallic active center relays catalysis, effectively regulating the conversion of the oxidation intermediates, and further improving the conversion rate of the reactants. The Co(II)&Zn(II)&Cu(II) doped hydrotalcite material provided by the present invention not only has the advantages of trimetallic active centers, high catalytic efficiency, good selectivity, etc., but also has a simple preparation method and low cost. The provided catalytic oxidation method of cycloalkanes has the advantages of high selectivity for cycloalkyl alcohols and cycloalkyl ketones, low reaction temperature, and few by-products. It is an efficient, feasible, and safe method for selective catalytic oxidation of cycloalkanes to synthesize cycloalkyl alcohols and cycloalkyl ketones. Summary of the invention
[0005] In view of the above technical problems existing in the prior art, the object of the present invention is to provide a Co(II)&Zn(II)&Cu(II) doped hydrotalcite and a preparation method thereof and an application thereof in catalytic oxidation of cycloalkanes to synthesize cycloalkyl alcohols and cycloalkyl ketones.
[0006] The method for preparing Co(II)&Zn(II)&Cu(II) doped hydrotalcite is characterized in that the hydrotalcite is mixed with Co(II) salt, Zn(II) salt and Cu(II) salt, and then placed in a ball mill for ball milling at room temperature. The granular powder product after ball milling is placed in a N2 atmosphere for high temperature treatment, cooled, and the product is stirred and washed with a 0.5~10.0 mol / L hydrochloric acid aqueous solution for 1.0~10.0 h, filtered, washed with water to a pH value of 3.0~8.0, and vacuum dried to obtain Co(II)&Zn(II)&Cu(II) doped hydrotalcite.
[0007] The hydrotalcite is magnesium aluminum carbonate type hydrotalcite Mg6A l2 (OH) 16 CO3·4H2O.
[0008] The method for preparing a Co(II) & Zn(II) & Cu(II) doped hydrotalcite is characterized in that the Co(II) salt is at least one of Co(CH3COO)2, Co(NO2)2, CoSO4, CoCl2 and hydrates thereof, or a mixture of two or more thereof in any proportion; the Zn(II) salt is at least one of Zn(CH3COO)2, Zn(NO2)2, ZnSO4, ZnCl2 and hydrates thereof, or a mixture of two or more thereof in any proportion; the Cu(II) salt is at least one of Cu(CH3COO)2, Cu(NO2)2, CuSO4, CuCl2 and hydrates thereof, or a mixture of two or more thereof in any proportion;
[0009] The ratio of the total amount of the metal ions of Co(II), Zn(II) and Cu(II) to the mass of the hydrotalcite is 0.001-0.500:1.0, preferably 0.002-0.005:1.0, the unit of the amount of the substance is mol, and the unit of mass is g.
[0010] The method for preparing Co(II)&Zn(II)&Cu(II)-doped hydrotalcite is characterized in that the ball milling speed is 600~900 rpm, the ball milling time is 1.0~20.0 h, preferably 5.0~15.0 h; the product after high temperature treatment and cooling is stirred and washed with 1.5~3.0 mol / L hydrochloric acid aqueous solution for 5.0~8.0 h, filtered, washed with water to a pH value of 5.0~7.0, and vacuum dried to obtain Co(II)&Zn(II)&Cu(II)-doped hydrotalcite.
[0011] The method for preparing Co(II) & Zn(II) & Cu(II) doped hydrotalcite is characterized in that the molar ratio of the Co(II) salt, the Zn(II) salt and the Cu(II) salt is 1.0: 0.1~3.0: 0.1~3.0, preferably 1.0: 0.5~2.5: 0.5~2.5.
[0012] The method for preparing Co(II)&Zn(II)&Cu(II) doped hydrotalcite is characterized in that the high temperature treatment temperature is 300~800°C, and the high temperature treatment time is 1.0~10.0 h, preferably 1.0~5.0 h.
[0013] Co(II)&Zn(II)&Cu(II) doped hydrotalcite prepared according to the above method.
[0014] The application of Co(II)&Zn(II)&Cu(II) doped hydrotalcite in the catalytic oxidation reaction of cycloalkanes is characterized in that the application method is as follows: dispersing Co(II)&Zn(II)&Cu(II) doped hydrotalcite in cycloalkanes, adding the obtained reaction mixture into a stainless steel high-pressure reactor with a polytetrafluoroethylene liner, sealing the reaction system, heating to the reaction temperature under stirring, introducing an oxidant and stirring the reaction for a period of time; cooling to room temperature after the reaction is completed, adding triphenylphosphine to the reaction solution, stirring at room temperature for 30 to 40 minutes to reduce the generated peroxide, that is, reacting to generate the final reaction products cycloalkyl alcohol and cycloalkyl ketone.
[0015] The use of the Co(II) & Zn(II) & Cu(II) doped hydrotalcite in the catalytic oxidation reaction of cycloalkane is characterized in that the cycloalkane is at least one of cyclopentane, cyclohexane, cycloheptane, cyclooctane, cyclononane, cyclodecane, and cyclododecane, or a mixture of two or more in any proportion; the ratio of the mass of the Co(II) & Zn(II) & Cu(II) doped hydrotalcite to the amount of cycloalkane is 1:5~20, preferably 1:8~12, the unit of mass is g, and the unit of amount of substance is mol.
[0016] The use of the Co(II)&Zn(II)&Cu(II) doped hydrotalcite in the catalytic oxidation of cycloalkanes is characterized in that the oxidant is oxygen, air or a mixture thereof in any proportion;
[0017] When the oxidant is introduced and stirred for reaction, the reaction temperature is 80-160°C, preferably 80-140°C; the reaction pressure is 0.1-2.0 MPa, preferably 0.6-1.2 MPa; the stirring reaction time is 2.0-24.0 h, preferably 8.0-16.0 h; and the stirring rate is 600-1200 rpm, preferably 800-1000 rpm.
[0018] The application of the Co(II)&Zn(II)&Cu(II) doped hydrotalcite in the catalytic oxidation of cycloalkane is characterized in that the molar amount of the triphenylphosphine is 2-4% of the molar amount of the cycloalkane raw material. A small amount of peroxide is generated in the reaction solution after the oxidant is stirred and reacted. The purpose of adding triphenylphosphine for reduction reaction in the present invention is to reduce the peroxide byproduct to the product cycloalkyl alcohol, thereby increasing the selectivity of the product cycloalkyl alcohol.
[0019] The present invention uses Co(II)&Zn(II)&Cu(II) doped hydrotalcite to construct a trimetallic relay catalytic system, and synergistically catalyzes the oxidation of cycloalkanes by O2 to synthesize cycloalkyl alcohols and cycloalkyl ketones, which not only effectively inhibits the disordered diffusion of free radicals in the oxidation process, but also realizes the catalytic conversion of the oxidation intermediate cycloalkyl hydroperoxide, greatly improves the selectivity of the target products cycloalkyl alcohols and cycloalkyl ketones, reduces the generation of by-products, and reduces the emission of environmental pollutants, which meets the current chemical industry's practical needs for "energy conservation and emission reduction". The present invention not only provides an efficient trimetallic catalytic material, but also provides a method for efficiently and selectively oxidizing the CH bonds of cycloalkanes to synthesize cycloalkyl alcohols and cycloalkyl ketones, and has a certain reference value for the selective catalytic oxidation of the CH bonds of other hydrocarbons and the efficient preparation of alcohols and ketone compounds.
[0020] The beneficial effects of the present invention are mainly reflected in: the Co(II)&Zn(II)&Cu(II) doped hydrotalcite of the present invention is simple to prepare, low in cost, and easy to apply industrially. The method of synthesizing cycloalkyl alcohols and cycloalkyl ketones by synergistic catalytic oxidation of cycloalkanes by the obtained catalytic material has the advantages of high selectivity of cycloalkyl alcohols and cycloalkyl ketones, low reaction temperature, few by-products, and small environmental impact. In addition, the content of cycloalkyl hydroperoxides of the present invention is low and the safety factor is high. The present invention provides an efficient, feasible and safe method for synthesizing cycloalkyl alcohols and cycloalkyl ketones by selective catalytic oxidation of cycloalkanes. DETAILED DESCRIPTION
[0021] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0022] Examples 1 to 21 are synthesis cases of Co(II)&Zn(II)&Cu(II) doped hydrotalcite;
[0023] Examples 22 to 60 are application cases of the materials in the catalytic oxidation of cycloalkanes;
[0024] Examples 61 to 64 are comparative experimental cases of catalytic oxidation of cycloalkanes;
[0025] Example 65 is a scaled-up experiment of catalytic oxidation of cycloalkanes by Co(II)&Zn(II)&Cu(II) doped hydrotalcite;
[0026] The hydrotalcite used in the embodiment of the present invention is magnesium aluminum carbonate type hydrotalcite Mg6A l2 (OH) 16 CO3·4H2O.
[0027] Example 1
[0028] 2.6553 g (15.00 mmol) of anhydrous cobalt acetate, 1.3763 g (7.50 mmol) of anhydrous zinc acetate, 1.4974 g (7.50 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill. The ball mill speed was 800 rpm and the ball mill was milled at room temperature for 8.0 h. The granular powder was dried in the shade at room temperature for 24.0 h and then treated at 500 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 9.7396 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs. 2.0:1.0:1.0 -500-2.0 (the molar ratio of Co, Zn and Cu is 2.0: 1.0: 1.0, 500 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0029] Example 2
[0030] 2.6553 g (15.00 mmol) of anhydrous cobalt acetate, 1.3763 g (7.50 mmol) of anhydrous zinc acetate, 1.4974 g (7.50 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill. The ball mill speed was 800 rpm and the ball mill was milled at room temperature for 8.0 h. The obtained granular powder was dried in the shade at room temperature for 24.0 h and then treated at 300 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 11.3695 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs. 2.0:1.0:1.0 -300-2.0 (the molar ratio of Co, Zn, and Cu is 2.0: 1.0: 1.0, 300 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0031] Example 3
[0032] 2.6553 g (15.00 mmol) of anhydrous cobalt acetate, 1.3763 g (7.50 mmol) of anhydrous zinc acetate, 1.4974 g (7.50 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill with a ball mill speed of 800 rpm for 8.0 h at room temperature. The obtained granular powder was dried in the shade at room temperature for 24.0 h and then treated at 700 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 8.0416 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs. 2.0:1.0:1.0 -700-2.0 (the molar ratio of Co, Zn and Cu is 2.0: 1.0: 1.0, 700 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0033] Example 4
[0034] 2.1242 g (12.00 mmol) of anhydrous cobalt acetate, 2.2022 g (12.00 mmol) of anhydrous zinc acetate, 1.1979 g (6.00 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill. The ball mill speed was 800 rpm and the ball mill was carried out at room temperature for 8.0 h. The obtained granular powder was dried in the shade at room temperature for 24.0 h and then treated at 500 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 10.0215 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs. 2.0:2.0:1.0 -500-2.0 (the molar ratio of Co, Zn, and Cu is 2.0: 2.0: 1.0, 500 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0035] Example 5
[0036] 2.1242 g (12.00 mmol) of anhydrous cobalt acetate, 2.2022 g (12.00 mmol) of anhydrous zinc acetate, 1.1979 g (6.00 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill. The ball mill speed was 800 rpm and the ball mill was carried out at room temperature for 8.0 h. The granular powder was dried in the shade at room temperature for 24.0 h and then treated at 300 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 11.7659 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs. 2.0:2.0:1.0 -300-2.0 (the molar ratio of Co, Zn, and Cu is 2.0: 2.0: 1.0, 300 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0037] Example 6
[0038] 2.1242 g (12.00 mmol) of anhydrous cobalt acetate, 2.2022 g (12.00 mmol) of anhydrous zinc acetate, 1.1979 g (6.00 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill. The ball mill speed was 800 rpm and the ball mill was carried out at room temperature for 8.0 h. The granular powder was dried in the shade at room temperature for 24.0 h and then treated at 700 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 9.3647 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs. 2.0:2.0:1.0 -700-2.0 (the molar ratio of Co, Zn and Cu is 2.0: 2.0: 1.0, 700 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0039] Example 7
[0040] 2.1242 g (12.00 mmol) of anhydrous cobalt acetate, 1.1011 g (6.00 mmol) of anhydrous zinc acetate, 2.3958 g (12.00 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill. The ball mill speed was 800 rpm and the ball mill was milled at room temperature for 8.0 h. The granular powder was dried in the shade at room temperature for 24.0 h and then treated at 500 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 11.0246 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs. 2.0:1.0:2.0 -500-2.0 (the molar ratio of Co, Zn and Cu is 2.0: 1.0: 2.0, 500 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0041] Example 8
[0042] 2.1242 g (12.00 mmol) of anhydrous cobalt acetate, 1.1011 g (6.00 mmol) of anhydrous zinc acetate, 2.3958 g (12.00 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill. The ball mill speed was 800 rpm and the ball mill was milled at room temperature for 8.0 h. The granular powder was dried in the shade at room temperature for 24.0 h and then treated at 300 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 12.1853 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs. 2.0:1.0:2.0 -300-2.0 (the molar ratio of Co, Zn, and Cu is 2.0: 1.0: 2.0, 300 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0043] Example 9
[0044] 2.1242 g (12.00 mmol) of anhydrous cobalt acetate, 1.1011 g (6.00 mmol) of anhydrous zinc acetate, 2.3958 g (12.00 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill. The ball mill speed was 800 rpm and the ball mill was milled at room temperature for 8.0 h. The granular powder was dried in the shade at room temperature for 24.0 h and then treated at 700 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 9.2418 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs. 2.0:1.0:2.0 -700-2.0 (the molar ratio of Co, Zn and Cu is 2.0: 1.0: 2.0, 700 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0045] Example 10
[0046] 1.0621 g (6.00 mmol) of anhydrous cobalt acetate, 2.2022 g (12.00 mmol) of anhydrous zinc acetate, 2.3958 g (12.00 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill with a ball mill speed of 800 rpm for 8.0 h at room temperature. The obtained granular powder was dried in the shade at room temperature for 24.0 h and then treated at 500 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 9.3124 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs. 1.0:2.0:2.0 -500-2.0 (the molar ratio of Co, Zn and Cu is 1.0: 2.0: 2.0, 500 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0047] Embodiment 11
[0048] 1.0621 g (6.00 mmol) of anhydrous cobalt acetate, 2.2022 g (12.00 mmol) of anhydrous zinc acetate, 2.3958 g (12.00 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill. The ball mill speed was 800 rpm and the ball mill was milled at room temperature for 8.0 h. The obtained granular powder was dried in the shade at room temperature for 24.0 h and then treated at 300 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 10.6357 g Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs 1.0:2.0:2.0 -300-2.0 (the molar ratio of Co, Zn and Cu is 1.0: 2.0: 2.0, 300 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0049] Example 12
[0050] 1.0621 g (6.00 mmol) of anhydrous cobalt acetate, 2.2022 g (12.00 mmol) of anhydrous zinc acetate, 2.3958 g (12.00 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill. The ball mill speed was 800 rpm and the ball mill was milled at room temperature for 8.0 h. The granular powder was dried in the shade at room temperature for 24.0 h and then treated at 700 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 8.9768 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs. 1.0:2.0:2.0 -700-2.0 (the molar ratio of Co, Zn and Cu is 1.0: 2.0: 2.0, 700 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0051] Example 13
[0052] 1.7702 g (10.00 mmol) of anhydrous cobalt acetate, 1.8351 g (10.00 mmol) of anhydrous zinc acetate, 1.9965 g (10.00 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill. The ball mill speed was 800 rpm and the ball mill was milled at room temperature for 8.0 h. The granular powder was dried in the shade at room temperature for 24.0 h and then treated at 500 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 9.4217 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs. 1.0:1.0:1.0 -500-2.0 (the molar ratio of Co, Zn and Cu is 1.0:1.0:1.0, 500 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0053] Embodiment 14
[0054] 1.7702 g (10.00 mmol) of anhydrous cobalt acetate, 1.8351 g (10.00 mmol) of anhydrous zinc acetate, 1.9965 g (10.00 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill. The ball mill speed was 800 rpm and the ball mill was milled at room temperature for 8.0 h. The granular powder was dried in the shade at room temperature for 24.0 h and then treated at 300 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 10.8731 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs. 1.0:1.0:1.0 -300-2.0 (the molar ratio of Co, Zn and Cu is 1.0:1.0:1.0, 300 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0055] Embodiment 15
[0056] 1.7702 g (10.00 mmol) of anhydrous cobalt acetate, 1.8351 g (10.00 mmol) of anhydrous zinc acetate, 1.9965 g (10.00 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill. The ball mill speed was 800 rpm and the ball milling was carried out at room temperature for 8.0 h. The granular powder was dried in the shade at room temperature for 24.0 h and then treated at 700 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 9.1035 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs. 1.0:1.0:1.0 -700-2.0 (the molar ratio of Co, Zn and Cu is 1.0: 1.0: 1.0, 700 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0057] Example 16
[0058] 1.3277 g (7.50 mmol) of anhydrous cobalt acetate, 2.7527 g (15.00 mmol) of anhydrous zinc acetate, 1.4974 g (7.50 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill with a ball mill speed of 800 rpm for 8.0 h at room temperature. The obtained granular powder was dried in the shade at room temperature for 24.0 h and then treated at 500 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 11.2011 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs 1.0:2.0:1.0 -500-2.0 (the molar ratio of Co, Zn and Cu is 1.0: 2.0: 1.0, 500 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0059] Embodiment 17
[0060] 1.3277 g (7.50 mmol) of anhydrous cobalt acetate, 2.7527 g (15.00 mmol) of anhydrous zinc acetate, 1.4974 g (7.50 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill with a ball mill speed of 800 rpm for 8.0 h at room temperature. The obtained granular powder was dried in the shade at room temperature for 24.0 h and then treated at 300 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 12.1469 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs. 1.0:2.0:1.0 -300-2.0 (the molar ratio of Co, Zn and Cu is 1.0: 2.0: 1.0, 300 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0061] Embodiment 18
[0062] 1.3277 g (7.50 mmol) of anhydrous cobalt acetate, 2.7527 g (15.00 mmol) of anhydrous zinc acetate, 1.4974 g (7.50 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill with a ball mill speed of 800 rpm for 8.0 h at room temperature. The obtained granular powder was dried in the shade at room temperature for 24.0 h and then treated at 700 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 9.0876 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs. 1.0:2.0:1.0 -700-2.0 (the molar ratio of Co, Zn and Cu is 1.0: 2.0: 1.0, 700 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0063] Embodiment 19
[0064] 1.3277 g (7.50 mmol) of anhydrous cobalt acetate, 1.3763 g (7.50 mmol) of anhydrous zinc acetate, 2.9948 g (15.00 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill with a ball mill speed of 800 rpm for 8.0 h at room temperature. The obtained granular powder was dried in the shade at room temperature for 24.0 h and then treated at 500 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 10.8571 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs. 1.0:1.0:2.0 -500-2.0 (the molar ratio of Co, Zn and Cu is 1.0: 1.0: 2.0, 500 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0065] Embodiment 20
[0066] 1.3277 g (7.50 mmol) of anhydrous cobalt acetate, 1.3763 g (7.50 mmol) of anhydrous zinc acetate, 2.9948 g (15.00 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill with a ball mill speed of 800 rpm for 8.0 h at room temperature. The obtained granular powder was dried in the shade at room temperature for 24.0 h and then treated at 300 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 11.3178 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs. 1.0:1.0:2.0 -300-2.0 (the molar ratio of Co, Zn and Cu is 1.0: 1.0: 2.0, 300 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0067] Embodiment 21
[0068] 1.3277 g (7.50 mmol) of anhydrous cobalt acetate, 1.3763 g (7.50 mmol) of anhydrous zinc acetate, 2.9948 g (15.00 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill with a ball mill speed of 800 rpm for 8.0 h at room temperature. The obtained granular powder was dried in the shade at room temperature for 24.0 h and then treated at 700 °C for 2 h under N2 atmosphere. The obtained Co(II)&Zn(II)&Cu(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 9.2143 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs. 1.0:1.0:2.0 -700-2.0 (the molar ratio of Co, Zn and Cu is 1.0: 1.0: 2.0, 700 is the high temperature treatment temperature, and 2.0 is the high temperature treatment time).
[0069] Embodiment 22
[0070] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of the Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 1 was added. 2.0:1.0:1.0-500-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 800 rpm for 8.0 h at 120 ºC and 1.00 MPa oxygen pressure. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 7.83%, cyclohexanol selectivity 45.45%, cyclohexanone selectivity 49.39%, cyclohexyl hydroperoxide selectivity 1.67%, adipic acid selectivity 2.96%, glutaric acid selectivity 0.53%.
[0071] Embodiment 23
[0072] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of the Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 1 was added. 2.0:1.0:1.0 -500-2.0 was dispersed in 14.0280 g (200 mmol) of cyclopentane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclopentane conversion rate 5.84%, cyclopentanol selectivity 11.75%, cyclopentanone selectivity 49.03%, cyclopentyl hydroperoxide selectivity 12.74%, glutaric acid selectivity 24.38%, succinic acid selectivity 2.10%.
[0073] Embodiment 24
[0074] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of the Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 1 was added. 2.0:1.0:1.0-500-2.0 was dispersed in 19.6380 g (200 mmol) of cycloheptane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cycloheptane conversion rate 26.59%, cycloheptanol selectivity 9.22%, cycloheptanone selectivity 66.89%, cycloheptyl hydroperoxide selectivity 19.07%, pimelic acid selectivity 4.11%, adipic acid selectivity 0.71%.
[0075] Embodiment 25
[0076] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of the Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 1 was added. 2.0:1.0:1.0 -500-2.0 was dispersed in 22.4440 g (200 mmol) of cyclooctane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclooctane conversion rate 27.34%, cyclooctanol selectivity 34.25%, cyclooctanone selectivity 49.24%, cyclooctyl hydroperoxide selectivity 12.73%, suberic acid selectivity 3.12%, and pimelic acid selectivity 0.66%.
[0077] Embodiment 26
[0078] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of the Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 1 was added. 2.0:1.0:1.0-500-2.0 was dispersed in 33.6640 g (200 mmol) of cyclododecane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide generated was reduced by stirring at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclododecane conversion rate 32.14%, cyclododecanol selectivity 19.13%, cyclododecanone selectivity 48.79%, cyclododecyl hydroperoxide selectivity 32.08%, and no dodecanoic acid and undecanoic acid were detected.
[0079] Embodiment 27
[0080] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 2 were added. 2.0:1.0:1.0 -300-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 6.93%, cyclohexanol selectivity 41.56%, cyclohexanone selectivity 45.78%, cyclohexyl hydroperoxide selectivity 5.61%, adipic acid selectivity 5.43%, and glutaric acid selectivity 1.62%.
[0081] Embodiment 28
[0082] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 3 was added. 2.0:1.0:1.0-700-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 7.12%, cyclohexanol selectivity 42.32%, cyclohexanone selectivity 46.57%, cyclohexyl hydroperoxide selectivity 6.59%, adipic acid selectivity 3.18%, and glutaric acid selectivity 1.34%.
[0083] Embodiment 29
[0084] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 4 was added. 2.0:2.0:1.0 -500-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 6.25%, cyclohexanol selectivity 43.21%, cyclohexanone selectivity 46.86%, cyclohexyl hydroperoxide selectivity 4.25%, adipic acid selectivity 4.07%, and glutaric acid selectivity 1.61%.
[0085] Embodiment 30
[0086] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 5 was added. 2.0:2.0:1.0-300-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 4.75%, cyclohexanol selectivity 42.80%, cyclohexanone selectivity 44.21%, cyclohexyl hydroperoxide selectivity 6.87%, adipic acid selectivity 4.91%, and glutaric acid selectivity 1.21%.
[0087] Embodiment 31
[0088] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 6 was added. 2.0:2.0:1.0 -700-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 5.89%, cyclohexanol selectivity 42.98%, cyclohexanone selectivity 44.68%, cyclohexyl hydroperoxide selectivity 6.56%, adipic acid selectivity 3.87%, and glutaric acid selectivity 1.91%.
[0089] Embodiment 32
[0090] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 7 was added. 2.0:1.0:2.0-500-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 6.13%, cyclohexanol selectivity 44.68%, cyclohexanone selectivity 46.09%, cyclohexyl hydroperoxide selectivity 4.59%, adipic acid selectivity 3.55%, and glutaric acid selectivity 1.09%.
[0091] Embodiment 33
[0092] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 8 was added. 2.0:1.0:2.0 -300-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 4.54%, cyclohexanol selectivity 43.87%, cyclohexanone selectivity 46.02%, cyclohexyl hydroperoxide selectivity 5.78%, adipic acid selectivity 3.30%, and glutaric acid selectivity 1.03%.
[0093] Embodiment 34
[0094] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 9 was added. 2.0:1.0:2.0-700-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 5.94%, cyclohexanol selectivity 43.76%, cyclohexanone selectivity 45.23%, cyclohexyl hydroperoxide selectivity 5.31%, adipic acid selectivity 4.09%, and glutaric acid selectivity 1.61%.
[0095] Embodiment 35
[0096] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 10 was added. 1.0:2.0:2.0 -500-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 5.96%, cyclohexanol selectivity 43.62%, cyclohexanone selectivity 45.69%, cyclohexyl hydroperoxide selectivity 5.48%, adipic acid selectivity 3.94%, and glutaric acid selectivity 1.27%.
[0097] Embodiment 36
[0098] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of the Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 11 was added. 1.0:2.0:2.0-300-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 5.23%, cyclohexanol selectivity 42.99%, cyclohexanone selectivity 44.39%, cyclohexyl hydroperoxide selectivity 6.01%, adipic acid selectivity 4.85%, and glutaric acid selectivity 1.76%.
[0099] Embodiment 37
[0100] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 12 was added. 1.0:2.0:2.0 -700-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 5.01%, cyclohexanol selectivity 43.14%, cyclohexanone selectivity 44.73%, cyclohexyl hydroperoxide selectivity 7.91%, adipic acid selectivity 3.19%, and glutaric acid selectivity 1.03%.
[0101] Embodiment 38
[0102] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 13 was added. 1.0:1.0:1.0-500-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 4.98%, cyclohexanol selectivity 40.23%, cyclohexanone selectivity 43.26%, cyclohexyl hydroperoxide selectivity 9.86%, adipic acid selectivity 4.62%, and glutaric acid selectivity 2.03%.
[0103] Embodiment 39
[0104] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 14 was added. 1.0:1.0:1.0 -300-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 3.79%, cyclohexanol selectivity 40.74%, cyclohexanone selectivity 44.08%, cyclohexyl hydroperoxide selectivity 10.67%, adipic acid selectivity 3.57%, and glutaric acid selectivity 0.94%.
[0105] Embodiment 40
[0106] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 15 was added. 1.0:1.0:1.0-700-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 4.31%, cyclohexanol selectivity 41.21%, cyclohexanone selectivity 44.22%, cyclohexyl hydroperoxide selectivity 9.24%, adipic acid selectivity 4.28%, and glutaric acid selectivity 1.05%.
[0107] Embodiment 41
[0108] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 16 was added. 1.0:2.0:1.0 -500-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 5.24%, cyclohexanol selectivity 42.76%, cyclohexanone selectivity 46.25%, cyclohexyl hydroperoxide selectivity 6.72%, adipic acid selectivity 3.41%, and glutaric acid selectivity 0.86%.
[0109] Embodiment 42
[0110] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 17 was added. 1.0:2.0:1.0-300-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 4.76%, cyclohexanol selectivity 43.62%, cyclohexanone selectivity 44.87%, cyclohexyl hydroperoxide selectivity 4.56%, adipic acid selectivity 5.90%, and glutaric acid selectivity 1.05%.
[0111] Embodiment 43
[0112] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 18 was added. 1.0:2.0:1.0 -700-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120°C, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 5.07%, cyclohexanol selectivity 43.89%, cyclohexanone selectivity 44.98%, cyclohexyl hydroperoxide selectivity 5.17%, adipic acid selectivity 5.31%, and glutaric acid selectivity 0.65%.
[0113] Embodiment 44
[0114] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 19 was added. 1.0:1.0:2.0-500-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.20 MPa. The reaction was stirred at 120°C, 0.80 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 5.06%, cyclohexanol selectivity 43.25%, cyclohexanone selectivity 45.71%, cyclohexyl hydroperoxide selectivity 5.49%, adipic acid selectivity 4.58%, and glutaric acid selectivity 0.97%.
[0115] Embodiment 45
[0116] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 20 was added. 1.0:1.0:2.0 -300-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120°C, 1.20 MPa oxygen pressure, and 800 rpm for 4.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 3.78%, cyclohexanol selectivity 42.75%, cyclohexanone selectivity 44.89%, cyclohexyl hydroperoxide selectivity 7.89%, adipic acid selectivity 4.02%, and glutaric acid selectivity 0.45%.
[0117] Embodiment 46
[0118] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 21 was added. 1.0:1.0:2.0-700-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120°C, 1.00 MPa oxygen pressure, and 800 rpm for 4.0 h. After the reaction was completed, ice water was cooled to room temperature, and 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 4.61%, cyclohexanol selectivity 42.51%, cyclohexanone selectivity 44.31%, cyclohexyl hydroperoxide selectivity 6.73%, adipic acid selectivity 5.68%, and glutaric acid selectivity 0.77%.
[0119] Embodiment 47
[0120] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0050 g of the Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 1 was added. 2.0:1.0:1.0 -500-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120°C, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 3.34%, cyclohexanol selectivity 38.46%, cyclohexanone selectivity 41.21%, cyclohexyl hydroperoxide selectivity 10.82%, adipic acid selectivity 6.31%, and glutaric acid selectivity 3.20%.
[0121] Embodiment 48
[0122] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0100 g of the Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 2 was added. 2.0:1.0:1.0-300-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120°C, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 5.81%, cyclohexanol selectivity 36.84%, cyclohexanone selectivity 43.26%, cyclohexyl hydroperoxide selectivity 11.58%, adipic acid selectivity 5.97%, and glutaric acid selectivity 2.35%.
[0123] Embodiment 49
[0124] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0300 g of Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 3 was added. 2.0:1.0:1.0 -700-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120°C, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 7.02%, cyclohexanol selectivity 40.56%, cyclohexanone selectivity 45.71%, cyclohexyl hydroperoxide selectivity 6.15%, adipic acid selectivity 5.77%, and glutaric acid selectivity 1.81%.
[0125] Embodiment 50
[0126] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0400 g of the Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 1 was added. 2.0:1.0:1.0-500-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120°C, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 8.06%, cyclohexanol selectivity 41.85%, cyclohexanone selectivity 44.54%, cyclohexyl hydroperoxide selectivity 3.94%, adipic acid selectivity 6.51%, and glutaric acid selectivity 3.16%.
[0127] Embodiment 51
[0128] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of the Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 1 was added. 2.0:1.0:1.0 -500-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 80 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 80°C, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, and 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 0.49%, cyclohexanol selectivity 36.52%, cyclohexanone selectivity 38.27%, cyclohexyl hydroperoxide selectivity 23.79%, adipic acid selectivity 1.30%, and glutaric acid selectivity 0.12%.
[0129] Embodiment 52
[0130] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of the Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 1 was added. 2.0:1.0:1.0-500-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 100 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 100°C, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 3.82%, cyclohexanol selectivity 39.54%, cyclohexanone selectivity 40.75%, cyclohexyl hydroperoxide selectivity 16.95%, adipic acid selectivity 2.37%, and glutaric acid selectivity 0.39%.
[0131] Embodiment 53
[0132] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of the Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 1 was added. 2.0:1.0:1.0 -500-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 140 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 140°C, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 8.21%, cyclohexanol selectivity 40.83%, cyclohexanone selectivity 45.92%, cyclohexyl hydroperoxide selectivity 4.98%, adipic acid selectivity 6.21%, and glutaric acid selectivity 2.06%.
[0133] Embodiment 54
[0134] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of the Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 1 was added. 2.0:1.0:1.0-500-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 0.80 MPa. The reaction was stirred at 120°C, 0.80 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 7.31%, cyclohexanol selectivity 44.75%, cyclohexanone selectivity 48.79%, cyclohexyl hydroperoxide selectivity 3.21%, adipic acid selectivity 2.12%, and glutaric acid selectivity 1.13%.
[0135] Embodiment 55
[0136] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of the Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 1 was added. 2.0:1.0:1.0 -500-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.20 MPa. The reaction was stirred at 120°C, 1.20 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 7.68%, cyclohexanol selectivity 43.69%, cyclohexanone selectivity 47.95%, cyclohexyl hydroperoxide selectivity 4.02%, adipic acid selectivity 3.31%, and glutaric acid selectivity 1.03%.
[0137] Embodiment 56
[0138] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of the Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 1 was added. 2.0:1.0:1.0-500-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120°C, 1.00 MPa oxygen pressure, and 800 rpm for 4.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 4.91%, cyclohexanol selectivity 41.81%, cyclohexanone selectivity 45.13%, cyclohexyl hydroperoxide selectivity 8.34%, adipic acid selectivity 3.93%, and glutaric acid selectivity 0.79%.
[0139] Embodiment 57
[0140] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of the Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 1 was added. 2.0:1.0:1.0 -500-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120°C, 1.00 MPa oxygen pressure, and 800 rpm for 6.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 5.22%, cyclohexanol selectivity 42.52%, cyclohexanone selectivity 44.84%, cyclohexyl hydroperoxide selectivity 7.06%, adipic acid selectivity 4.57%, and glutaric acid selectivity 1.01%.
[0141] Embodiment 58
[0142] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of the Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 1 was added. 2.0:1.0:1.0-500-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120°C, 1.00 MPa oxygen pressure, and 800 rpm for 10.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 6.93%, cyclohexanol selectivity 43.55%, cyclohexanone selectivity 46.31%, cyclohexyl hydroperoxide selectivity 5.62%, adipic acid selectivity 3.65%, and glutaric acid selectivity 0.87%.
[0143] Embodiment 59
[0144] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of the Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 1 was added. 2.0:1.0:1.0 -500-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120°C, 1.00 MPa oxygen pressure, and 800 rpm for 16.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 7.95%, cyclohexanol selectivity 42.59%, cyclohexanone selectivity 48.16%, cyclohexyl hydroperoxide selectivity 2.01%, adipic acid selectivity 5.67%, and glutaric acid selectivity 1.57%.
[0145] Embodiment 60
[0146] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of the Co(II)&Zn(II)&Cu(II)-doped hydrotalcite LDHs prepared in Example 1 was added. 2.0:1.0:1.0-500-2.0 was dispersed in 16.8320 g (200 mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120°C, 1.00 MPa oxygen pressure, and 800 rpm for 24.0 h. After the reaction was completed, ice water was cooled to room temperature, 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 8.51%, cyclohexanol selectivity 40.82%, cyclohexanone selectivity 47.65%, cyclohexyl hydroperoxide selectivity 1.42%, adipic acid selectivity 7.34%, and glutaric acid selectivity 2.77%.
[0147] Example 61 (Comparative Experiment)
[0148] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of hydrotalcite was dispersed in 16.8320 g (200 mmol) of cyclohexane, the autoclave was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120 ºC, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, and 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 0.24%, cyclohexanol selectivity 11.62%, cyclohexanone selectivity 20.13%, cyclohexyl hydroperoxide selectivity 68.25%, and no adipic acid and glutaric acid were detected.
[0149] Example 62 (Comparative Experiment)
[0150] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0100 g of anhydrous cobalt acetate, 0.0100 g of anhydrous zinc acetate, and 0.0100 g of anhydrous copper acetate were dispersed in 16.8320 g (200 mmol) of cyclohexane, the autoclave was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120°C, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, and 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the generated peroxide was reduced by stirring at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 3.03%, cyclohexanol selectivity 27.21%, cyclohexanone selectivity 22.58%, cyclohexyl hydroperoxide selectivity 48.61%, adipic acid selectivity 1.39%, glutaric acid selectivity 0.21%.
[0151] Example 63 (Comparative Experiment)
[0152] 2.6553 g (15.00 mmol) of anhydrous cobalt acetate, 1.3763 g (7.50 mmol) of anhydrous zinc acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill. The mixture was ball milled at 800 rpm at room temperature for 8.0 h. The obtained granular powder was dried in the shade at room temperature for 24.0 h and then treated at 500 °C for 2 h under N2 atmosphere. The obtained Co(II) & Zn(II) doped hydrotalcite material was stirred and washed in 50.0 mL of hydrochloric acid aqueous solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain Co(II) & Zn(II) doped hydrotalcite.
[0153] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of the above-prepared Co(II)&Zn(II)-doped hydrotalcite was dispersed in 16.8320 g (200 mmol) of cyclohexane, the autoclave was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120°C, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, and 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the generated peroxide was reduced by stirring at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 4.31%, cyclohexanol selectivity 38.72%, cyclohexanone selectivity 42.35%, cyclohexyl hydroperoxide selectivity 10.85%, adipic acid selectivity 6.02%, glutaric acid selectivity 2.06%.
[0154] Example 64 (Comparative Experiment)
[0155] 2.6553 g (15.00 mmol) of anhydrous cobalt acetate, 1.4974 g (7.50 mmol) of anhydrous copper acetate and 10.0 g of hydrotalcite were mixed and placed in a 50 mL agate ball mill. The mixture was ball milled at 800 rpm at room temperature for 8.0 h. The obtained granular powder was dried in the shade at room temperature for 24.0 h and then treated at 500 °C for 2 h under N2 atmosphere. The obtained Co(II)&Cu(II)-doped hydrotalcite material was stirred and washed in 50.0 mL of aqueous hydrochloric acid solution (2.0 mol / L) for 6.0 h, filtered, washed with water until the pH value was 5.0-7.0, and dried in vacuum to obtain 9.7396 g of Co(II)&Cu(II)-doped hydrotalcite.
[0156] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of the above-prepared Co(II)&Cu(II)-doped hydrotalcite was dispersed in 16.8320 g (200 mmol) of cyclohexane, the autoclave was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120°C, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, and 1.3115 g (5.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the generated peroxide was reduced by stirring at room temperature for 30 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 4.22%, cyclohexanol selectivity 39.24%, cyclohexanone selectivity 43.28%, cyclohexyl hydroperoxide selectivity 14.31%, adipic acid selectivity 2.06%, glutaric acid selectivity 1.11%.
[0157] Example 65 (Enlargement Experiment)
[0158] In a 1 L stainless steel autoclave with a polytetrafluoroethylene liner, 0.2000 g of Co(II)&Zn(II)&Cu(II) doped hydrotalcite LDHs prepared in Example 1 was added. 2.0:1.0:1.0 -500-2.0 was dispersed in 168.3200 g (2.0 mol) of cyclohexane, the reactor was sealed, the temperature was raised to 120 ºC with stirring, and oxygen was introduced to 1.00 MPa. The reaction was stirred at 120°C, 1.00 MPa oxygen pressure, and 800 rpm for 8.0 h. After the reaction was completed, ice water was cooled to room temperature, and 13.115 g (50.00 mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced at room temperature for 50 min to obtain the final reaction product. The final reaction product was analyzed and tested, and the calculated reaction results were: cyclohexane conversion rate 7.65%; cyclohexanol selectivity 45.01%, cyclohexanone selectivity 48.74%, adipic acid selectivity 3.05%, glutaric acid selectivity 0.32%.
[0159] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.
Claims
1. Application of Co(II)&Zn(II)&Cu(II) doped hydrotalcite in catalytic oxidation of cycloalkanes, characterized in that The preparation method of the Co(II)&Zn(II)&Cu(II) doped hydrotalcite is as follows: after mixing the hydrotalcite with Co(II) salt, Zn(II) salt and Cu(II) salt, the mixture is placed in a ball mill and ball milled at room temperature, wherein the rotation speed of the ball mill is 600-900 rpm and the ball milling time is 5.0-15.0 h. The granular powder product after ball milling is placed in a N2 atmosphere for high temperature treatment, cooled, and the product is stirred and washed with a 0.5-10.0 mol / L hydrochloric acid aqueous solution for 1.0-10.0 h, filtered, washed with water until the pH value is 3.0-8.0, and vacuum dried to obtain the Co(II)&Zn(II)&Cu(II) doped hydrotalcite; The high temperature treatment temperature is 300-800° C., and the high temperature treatment time is 1.0-10.0 h.
2. The use of Co(II) & Zn(II) & Cu(II) doped hydrotalcite in catalytic oxidation of cycloalkanes as claimed in claim 1, characterized in that: The Co(II) salt is at least one of Co(CH3COO)2, Co(NO2)2, CoSO4, CoCl2 and hydrates thereof, or a mixture of two or more thereof in any proportion; the Zn(II) salt is at least one of Zn(CH3COO)2, Zn(NO2)2, ZnSO4, ZnCl2 and hydrates thereof, or a mixture of two or more thereof in any proportion; the Cu(II) salt is at least one of Cu(CH3COO)2, Cu(NO2)2, CuSO4, CuCl2 and hydrates thereof, or a mixture of two or more thereof in any proportion; The ratio of the total amount of metal ions of Co(II), Zn(II) and Cu(II) to the mass of hydrotalcite is 0.001-0.500:1.0, the unit of the amount of substance is mol, and the unit of mass is g.
3. The use of Co(II) & Zn(II) & Cu(II) doped hydrotalcite in catalytic oxidation of cycloalkanes as claimed in claim 2, characterized in that: The ratio of the total amount of metal ions of Co(II), Zn(II) and Cu(II) to the mass of hydrotalcite is 0.002-0.005:1.0, the unit of the amount of substance is mol, and the unit of mass is g.
4. The use of Co(II) & Zn(II) & Cu(II) doped hydrotalcite in catalytic oxidation of cycloalkanes as claimed in claim 1, characterized in that: The product after high temperature treatment and cooling is stirred and washed with 1.5-3.0 mol / L hydrochloric acid aqueous solution for 5.0-8.0 h, filtered, washed with water until the pH value is 5.0-7.0, and vacuum dried to obtain Co(II)&Zn(II)&Cu(II) doped hydrotalcite.
5. The use of Co(II)&Zn(II)&Cu(II) doped hydrotalcite in catalytic oxidation of cycloalkanes as claimed in claim 1, characterized in that: The molar ratio of the Co(II) salt, the Zn(II) salt and the Cu(II) salt is 1.0: 0.1-3.0: 0.1-3.0, and the hydrotalcite is a magnesium aluminum carbonate type hydrotalcite Mg6Al2(OH) 16 CO3·4H2O.
6. The use of Co(II)&Zn(II)&Cu(II) doped hydrotalcite in catalytic oxidation of cycloalkanes as claimed in claim 5, characterized in that: The molar ratio of the Co(II) salt, the Zn(II) salt and the Cu(II) salt is 1.0: 0.5~2.5: 0.5~2.
5.
7. The use of Co(II)&Zn(II)&Cu(II) doped hydrotalcite in catalytic oxidation of cycloalkanes as claimed in claim 1, characterized in that: The high temperature treatment time is 1.0 to 5.0 h.
8. The use of Co(II) & Zn(II) & Cu(II) doped hydrotalcite in catalytic oxidation of cycloalkanes as claimed in claim 1, characterized in that: The application method is as follows: Co(II)&Zn(II)&Cu(II) doped hydrotalcite is dispersed in cycloalkane, the obtained reaction mixture is added into a stainless steel high-pressure reactor with a polytetrafluoroethylene liner, the reaction system is sealed, the temperature is raised to the reaction temperature under stirring, an oxidant is introduced and stirred for a period of time; after the reaction is completed, the reaction solution is cooled to room temperature, triphenylphosphine is added to the reaction solution, and the reaction solution is stirred at room temperature for 30 to 40 minutes to reduce the generated peroxide, that is, the reaction generates the final reaction products cycloalkyl alcohol and cycloalkyl ketone.
9. The use of Co(II) & Zn(II) & Cu(II) doped hydrotalcite in catalytic oxidation of cycloalkanes as claimed in claim 8, characterized in that: The cycloalkane is at least one of cyclopentane, cyclohexane, cycloheptane, cyclooctane, cyclononane, cyclodecane, and cyclododecane, or a mixture of two or more of them in any proportion; the mass ratio of the Co(II) & Zn(II) & Cu(II) doped hydrotalcite to the amount of cycloalkane is 1:5~20, the unit of mass is g, and the unit of amount of substance is mol.
10. The use of Co(II) & Zn(II) & Cu(II) doped hydrotalcite in catalytic oxidation of cycloalkanes as claimed in claim 9, characterized in that: The mass ratio of the Co(II)&Zn(II)&Cu(II) doped hydrotalcite to the amount of cycloalkane is 1:8-12, the unit of mass is g, and the unit of amount of substance is mol.
11. The use of Co(II) & Zn(II) & Cu(II) doped hydrotalcite in catalytic oxidation of cycloalkanes as claimed in claim 8, characterized in that: The oxidant is oxygen, air or any mixture thereof; When the oxidant is introduced and stirred for reaction, the reaction temperature is 80~160°C, the reaction pressure is 0.1~2.0 MPa, the stirring reaction time is 2.0~24.0 h, and the stirring rate is 600~1200 rpm.
12. The use of Co(II) & Zn(II) & Cu(II) doped hydrotalcite in catalytic oxidation of cycloalkanes as claimed in claim 11, characterized in that: When the oxidant is introduced and stirred for reaction, the reaction temperature is 80~140°C; the reaction pressure is 0.6~1.2MPa; the stirring reaction time is 8.0~16.0h; and the stirring rate is 800~1000 rpm.
13. The use of Co(II) & Zn(II) & Cu(II) doped hydrotalcite in catalytic oxidation of cycloalkanes as claimed in claim 8, characterized in that: The molar amount of triphenylphosphine is 2-4% of the molar amount of the cycloalkane raw material.
Citation Information
Patent Citations
Hydrophobic hydrotalcite-supported bimetallic catalyst and oxidation catalysis application thereof
CN108906053A
Method for catalytically oxidizing cycloalkane through three-metal-center (CoCuZn) 2D MOFs / ultraviolet light
CN113603564A